Criminal Liability in Mob Attack Crimes Committed by Children Resulting in Death (A Case Study of Decision Number 22/Pid.Sus-Anak/2018/PN Smg) - Satya Yovita Yogaswari; Wenny Megawati (Law and Justice, 2023)
Maraknya Anak melakukan perbuatan melawan hukum yang terjadi di masyarakat sebagai indikasi sosial yang mengganggu kehidupan bermasyarakat. Salah satu tindak pidana pada Anak yang pernah terjadi pada wilayah hukum Pengadilan Negeri Semarang dengan Putusan Nomor 22/Pid.Sus-Anak/2018/PN Smg sebagaimana anak pelaku tindak pidana pengeroyokan oleh anak yang mengakibatkan kematian. Atas perbuatan yang dilakukan maka hakim menerapkan sanksi pidana penjara kepada anak dengan pidana penjara selama 4 bulan. Tujuan penelitian ini untuk mengetahui pertanggungjawaban pidana dalam tindak pidana pengeroyokan oleh anak yang mengakibatkan kematian, serta dasar pertimbangan hukum bagi hakim dalam menjatuhkan putusan pidana terhadap pertanggungjawaban pidana dalam tindak pidana pengeroyokan oleh anak yang mengakibatkan kematian dalam Putusan Perkara Nomor: 22/Pid.Sus-Anak/2018/PN Smg. Jenis penelitian yang digunakan adalah penelitian yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus, yang didukung dengan data yang didapat dari data kepustakaan diantaranya buku-buku, peraturan perundang-undangan, serta Putusan Pengadilan. Data dikumpulkan dari sumber data sekunder dan sumber data primer, dimana data sekunder diperoleh dari bahan pustaka untuk mendukung atau menambah wawasan informasi, sedangkan sumber data primer berupa data pendukung tambahan wawancara.  Berdasarkan hasil penelitian bahwa pertanggungjawaban pidana dalam tindak pidana pengeroyokan oleh anak yang mengakibatkan kematian dapat dilihat pengaturannya dalam Undang-Undang pasal 170 ayat (2) ke-3 KUHP dengan mengikuti ketentuan pidana penjara pasal 79 UU SPPA. Anak dipidana dengan ancaman ½ (setengah) dari ketentuan pasal 170 ayat 2-3 KUHP. Kata Kunci :  Pengeroyokan, Anak, Pertanggungjawaban     The rise of children committing acts against the law that occur in society is a social indication that disrupts community life. One of the crimes against children that has occurred in the jurisdiction of the Semarang District Court with Decision Number 22/Pid.Sus-Anak/2018/PN Smg as the child who is the perpetrator of the crime of beating by a child which results in death. For the actions committed, the judge imposes prison sentences on children with imprisonment for 4 months. The purpose of this study is to determine criminal responsibility in the crime of beatings by children which results in death, as well as the legal basis for judges in imposing criminal decisions on criminal liability in the crime of beatings by children which results in death in Case Decision Number: 22/Pid.Sus-Anak/2018/PN Smg. The type of research used is normative juridical research with a statutory approach and a case approach, which is supported by data obtained from library data including books, laws and regulations, and court decisions. Data were collected from secondary data sources and primary data sources, where secondary data were obtained from library materials to support or add insight into information, while the primary data source was in the form of additional supporting data from interviews. Based on the results of the study, criminal responsibility in the crime of beatings by children which resulted in death can be seen in the provisions in Article 170 paragraph (2) of the 3rd Criminal Code by following the provisions of imprisonment in Article 79 of the SPPA Law. Children are punished with the threat of ½ (half) of the provisions of Article 170 paragraph 2 3 of the Criminal Code. Keywords: Beatings. Child, Accountability.